KOMUNIKASI MECARU SIAP SELEM SEBAGAI MEDIA RITUAL MENUTUP SUMUR DALAM UPACARA YADNYA DI LINGKUNGAN KARANG BARU UTARA KOTA MATARAM - I KOMANG WIDYA PURNAMA YASA (GANEC SWARA, 2022)
Communication in the perspective of religious ceremonies focuses on the processes that occur in it. The process creates an interaction that realizes the implementation of the black chicken mecaru (mecaru siap selem) as a ritual medium to close the water well in the yadnya ceremony at Karang Baru Utara environment of Mataram City. The ceremony is carried out when there are Hindus who no longer use wells as a source of water in their daily life. This study aims to determine the form of communication, the communication process and the meaning of communication of mecaru siap selem.The qualitative paradigm with a phenomenological approach is the study method in this research. Theories used to know the processes that occur in this ceremony are the theory of religion, symbolic interaction theory, phenomenology, and the theory of communicative action. The location of this research at Karang Baru Utara, Mataram.The results of this study indicate that the implementation of the mecaru siap selem can overcome phenomena that can occur. The communication forms of mecaru siap selem in the yadnya ceremony are symbolic communication, transcendent communication and interpersonal communication (interpersonal). The communication process is indicated by the availability of the offerings (bebantenan) as a means accompanied by a Priest and prayers to pray to Vishnu, equipped with the metabuh pecaruan process as a complement to this ceremony. The meaning of the communication of mecaru siap selem religious meaning and togetherness